The Relationship Between the Benton Face Recognition Test and Electrophysiological Unfamiliar Face Individuation Response as Revealed by Fast Periodic Stimulation. (February 2020) - Dzhelyova, Milena; Schiltz, Christine; Rossion, Bruno
A recent approach to implicitly study face recognition skills has been the fast periodic visual stimulation (FPVS) coupled with electroencephalography (EEG). Its relationship with explicit behavioral measures of face individuation remains largely undocumented. We evaluated the relationship of the FPVS–EEG measure of individuation and performance at a computer version of the Benton Face Recognition Test. High-density EEG was recorded in 32 participants presented with an unfamiliar face at a rate of 6 Hz (F) for 60 s. Every five faces, new identities were inserted. The resulting 1.2 Hz (F/5) EEG response and its harmonics objectively indexed rapid individuation of unfamiliar faces. The robust individuation response, observed over occipitotemporal sites, was significantly correlated with speed, but not accuracy rate of the computer version of the Benton Face Recognition Test. This effect was driven by a few individuals who were particularly slow at the behavioral test and also showed the lowest face individuation response. These results highlight the importance of considering the time taken to recognize a face, as a complementary to accuracy rate variable, providing valuable information about one's recognition skills. Overall, these observations strengthen the diagnostic value of FPVS–EEG as an objective and rapid flag for specific difficulties at individual face recognition in the human population.